DAYA TARIK DESA WISATA BUDAYA BOKOR KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Silva Fitra Lisa; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
An attraction that can attract tourists to visit must meet the development requirements, namely what to see, what to do, what to buy, what to arrive and what to stay. This study aims to determine the attractiveness of the Bokor Cultural Tourism Village and to determine the management of the Bokor Cultural Tourism Village, Meranti Islands Regency, Riau Province. The methodology used is a qualitative research method with a descriptive approach. This research was conducted with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the Bokor Cultural Tourism Village meets five development requirements, namely what to see, what to do, what to buy, what to arrive and what to stay. However, the implementation of these five conditions has not been fully maximized and these conditions do exist but are inadequate.Keywords: Attractiveness, Management, Bokor Village